2021
DOI: 10.1097/bpo.0000000000002011
|View full text |Cite
|
Sign up to set email alerts
|

Omitting the Early Postoperative Follow-up in Uncomplicated Operative Supracondylar Humerus Fractures in Children Does Not Negatively Affect Outcomes

Abstract: Background: Supracondylar humerus (SCH) fractures are the most common surgically treated elbow injuries in children. There have been debates regarding if an early postoperative follow-up before pin removal is necessary to decrease the complications related to surgical fixation. To date, studies examining this topic have included smaller sample sizes, limiting the generalizability of their findings. Methods: A retrospective chart review of outcomes after operative management of Gartland type II and III SCH frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In our study, the average humerocapitellar angle of all patients on the operated side was 41.97 ± 3.08 degrees. It is similar to the result in the study of 1,518 cases conducted by Boden et al [18].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the average humerocapitellar angle of all patients on the operated side was 41.97 ± 3.08 degrees. It is similar to the result in the study of 1,518 cases conducted by Boden et al [18].…”
Section: Discussionsupporting
confidence: 92%
“…16 The majority of recent papers on postoperative management of these fractures have focused on the questionable necessity of early follow-up (eg, at 1 week) and the value of follow-up after pin removal. [16][17][18][19][20][21] In all such papers, the average pin removal date was never longer than 28 days postoperatively in any group, and therefore despite a lack of robust literature evidence, this appears to be a widely used time period. Rutarama et al 22 showed good functional outcomes in a prospective cohort of 38 children with Gartland type III supracondylar fractures who were all immobilized for 3 weeks post reduction and K-wires, but there was no comparator group.…”
Section: Discussionmentioning
confidence: 99%
“…Some have suggested the lack of utility in bringing these children back for a 1 week check-up in uncomplicated cases but this has certainly not been applied in most centers, including those patients seen in the current study. 17,20 In comparing the effects of immobilization length on the outcome, the current paper, therefore, represents the first of its kind. Though it was not statistically significant, there was nearly a 4-week difference between the groups for the length of time followed up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation